Kampanye “Rehat Gadget” Guna Mengurangi Kecanduan Smartphone Bagi Remaja di Kota Jakarta - Dwi Nugroho, Ryan; Almanfaluthi, Betha (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2022)
This design has the aim of reducing the number of smartphone addiction in adolescents and also for the awareness of teenagers to be able to use smartphones wisely in order to avoid the many negative impacts caused by smartphones. The analytical method used in this design is 5W+1H, the main reason for this problem was found, namely because smartphones provide many features that can help daily activities so that users feel comfortable using a long duration. With this design, teenagers are able to raise awareness to reduce the use of smartphones and manage them properly.